Slope stability analysis using modified Fellenius’s and Bishop’s method - M.F., Zolkepli; Mohd Fakhrurrazi, Ishak; Zaini, M.S.I. (IOP Publishing Ltd., 2019)
Analysis of slope stability is very important as many structures in hilly areas failed due to instability of slope. The aim of this study is to determine the factor of safety (FOS) of slopes located at Pahang Matriculation College by using limit equilibrium method. Two methods known as modified Fellenius’s method and modified Bishop’s method are used in this study. Laboratory testing involving index and engineering properties are conducted to determine the properties of soil within the study area. The soil at Pahang Matriculation College can be classified as sandy SILT with high plasticity. From the analysis, the FOS values for two slopes in saturated soil conditions (0 kPa suction) are between 1.262-2.885 when using Bishop’s method which are higher compare to 1.199-2.688 when using Fellenius’s method. The percentage differences of FOS between these two methods are between 5.25% to 7.33%. For slopes in unsaturated conditions (20 kPa suctions), the FOS are between 1.550-3.702 when using modified Bishop’s method which always higher compare to 1.492-3.507 when using modified Fellenius’s method. The percentage differences of FOS are between 3.89% to 5.56%. The relative accuracy of Bishop’s method is due to it consider only the vertical equilibrium of each slices and there is no need to consider the horizontal components of the interslice forces without introducing serious error in the FOS value.